1988
DOI: 10.1164/ajrccm/138.2.395
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Mediators Involved in Antigen-induced Airway Microvascular Leakage in Guinea Pigs

Abstract: Antigen challenge of ovalbumin (OA)-sensitized guinea pigs results in significant (p less than 0.05) increases in vascular permeability to Evans blue (EB) dye in the airways, esophagus, and bladder. Mean values +/- SEM in ng EB/mg wet weight tissue for unsensitized versus sensitized animals were: trachea, 23.6 +/- 6.6 versus 92.5 +/- 11.1; main bronchi, 31.1 +/- 12.2 versus 153.1 +/- 14.9; "central" intrapulmonary airways (ipa), 34.6 +/- 11.2 versus 101.3 +/- 6.2; and "peripheral" ipa, 26.2 +/- 6.8 versus 93.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(43 citation statements)
references
References 1 publication
2
41
0
Order By: Relevance
“…31,32 We indeed observed that after intradermal injection of 5ϫ10 5 activated MC/9 cells in mice, vascular leakage as judged by Evans Blue spot size was significantly enhanced compared with PBS and was demonstrated to only be inhibited by the H 1 -receptor antagonist triprolidine (online-only Data Supplement Figure VII, PϽ0.001). More importantly, carotid artery lesions, perivascularly challenged with DNP and injected with Rhodamine 6G to label circulating leukocytes, contained a higher number of Rhodamine-positive cells than controls (Pϭ0.0002) ( Figure 7A) at 3 days after challenge.…”
Section: Microvascular Leakage In Vivomentioning
confidence: 90%
“…31,32 We indeed observed that after intradermal injection of 5ϫ10 5 activated MC/9 cells in mice, vascular leakage as judged by Evans Blue spot size was significantly enhanced compared with PBS and was demonstrated to only be inhibited by the H 1 -receptor antagonist triprolidine (online-only Data Supplement Figure VII, PϽ0.001). More importantly, carotid artery lesions, perivascularly challenged with DNP and injected with Rhodamine 6G to label circulating leukocytes, contained a higher number of Rhodamine-positive cells than controls (Pϭ0.0002) ( Figure 7A) at 3 days after challenge.…”
Section: Microvascular Leakage In Vivomentioning
confidence: 90%
“…Role of platelet-activating factor in allergic rhinitis Platelet-activating factor (PAF) is an important mediator of AR, as concluded from the effectiveness of the PAF antagonist ABT-491 in rat and guinea-pig models of AR [10,11]. The biological properties of this mediator include vasodilation and an increase in vascular permeability that may contribute to the appearance of rhinorrhoea and nasal congestion [12,13]. Both PAF and its metabolite, lyso-PAF, have been detected in the nasal fluids and plasma of patients with rhinitis [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…3,4) On the other hand, since pharmaceutical targets for new asthmatic drugs have become more immunologically diverse and specific, detailed immunological analysis of mechanisms in animal models is required to determine with precision the efficacies of new drug candidates. However, the guinea pig airway model is not sufficient for this purpose, since immunological and genetic research on guinea pigs has not been performed in detail.…”
mentioning
confidence: 99%